Kinerja Bidan Desa dalam Deteksi Dini Kasus Malaria pada Kehamilan di Kabupaten Bengkulu Tengah - Mizawati, Afrina; Hakimi, Moh; Kusnanto, Hari (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2016)
Background: Malaria has become the health problem that cause mortality especially in high risk group such as infants, children below 5 years old and pregnant women. The incidence of malaria in Central Bengkulu, Bengkulu Province is quite high, the last three years there is an increase compared to year 2011 – 2013. Annual Malaria Incidence in 2011 was 75.68/00, where the incidence in 2012 was 66.13/00. The Annual Parasite Incidence in 2013 was 52.34/00. In 2013, the amount of pregnant women who underwent malaria screening during 1st antenatal care (K1) only 784 from 2016 pregnant women(39%).Objective: To understand the malaria screening achievement among pregnant women by village midwives in Central Bengkulu District.Method: The study was observational with cross sectional design. The subjects was all of the village midwives in Central Bengkulu District. The dependent variable in this study was midwives achievement in malaria screening during pregnancy. The independent variables were training for malaria screening during pregnancy and the availability of rapid diagnostic test (RDT). The disturbing variables were age, level of education, and the duration of work. The study’s instrument was questionnare and observational sheet. The data analysis was done with t test, correlation method, chi square and linear regression.Result and Discussion: The achievement in malaria’s screening during pregnancy by village midwives was better in the group who received training compared with the group who didn’t (RR 2.2 ; 95% CI 1.71 – 2.51). The achievement also was better in the group of midwives who had good supply of RDT compared with the group who didn’t (RR 1.5; 95% CI 1.01 – 1.94).Conclusion: The achievement of malaria’s screening during pregnancy among village midwives who received training was better compared to midwives who didn’t. The achievement was also better among midwives who had good supply of RDT compared with midwives who didn’t. There is relation between level of midwivery education and the achievement in screening b ut there was no relation between age and duration of work and achievement during screening.Keywords: Achievement of Village Midwives, Screening, Training and Availability of RDT